2019
DOI: 10.48550/arxiv.1903.05593
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Smart Home Personal Assistants: A Security and Privacy Review

Jide S. Edu,
Jose M. Such,
Guillermo Suarez-Tangil

Abstract: Smart Home Personal Assistants (SPA) are an emerging innovation that is changing the means by which home users interact with technology. However, there are a number of elements that expose these systems to various risks: i) the open nature of the voice channel they use, ii) the complexity of their architecture, iii) the AI features they rely on, and iv) their use of a wide range of underlying technologies. This paper presents an in-depth review of the security and privacy issues in SPA, categorizing the most i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 63 publications
(83 reference statements)
0
7
0
1
Order By: Relevance
“…This ongoing access to information presents the dual issues of both identification of individuals and profiling, i.e. compiling and analysing data on the journalist and their identified sources [14,37,80]. Hypothetical consequences.…”
Section: Profiling Threatsmentioning
confidence: 99%
“…This ongoing access to information presents the dual issues of both identification of individuals and profiling, i.e. compiling and analysing data on the journalist and their identified sources [14,37,80]. Hypothetical consequences.…”
Section: Profiling Threatsmentioning
confidence: 99%
“…Many researches were done to crack open the device using voice directions into the voice assistant by using ultrasonic waves that also helps in answering the calls on the cellphone easily [19].When the hardware attacks take place on the cloud where the device information is stored. [3]. Whereas past studies, merchant investigations, and IT press looks to concentrate on hardware attacks, the results from a user perspective appear to be relegated to associate implicit circumstance.…”
Section: One Natural Concern Becomes What Else These Devices Hearmentioning
confidence: 99%
“…Users of smart speakers are asked to play music, get the weather forecast, or set a timer or an alarm. [3]Advancements are taking place a lot now in home improvement in Natural language processing and are resulting in development of highly performing networking models since the beginning of 21 st century. [4].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has highlighted privacy threats from always-on voice assistants. They have been extensively researched both in academia [1,16,24,11,5,2,19] and by the media [15]. Dubois et al [10] analysed misactivations with newscasts and TV shows and found 0.95 per hour, lasting for at least 10s.…”
Section: Voice Assistants and Mis-activationsmentioning
confidence: 99%